Use of an 'EZ‐blocker' to facilitate thoracoscopic surgery in two dogs. Issue 3 (7th August 2017) - Wang, Wen Hui; Diez Bernal, Sabina; Mirra, Alessandro; Levionnois, Olivier Louis Raymond; Raillard, Mathieu
Abstract : This report documents the practical introduction of an EZ‐blocker to achieve one‐lung ventilation in two medium‐sized dogs for video‐assisted thoracoscopic pericardiectomy and right caudal lung lobectomy. Bronchoscopy was performed after blind introduction of the device through the endotracheal tube at the level of the tracheobronchial bifurcation. The EZ‐blocker was successfully placed on the first attempt in the first case but initially remained trapped in the Murphy eye of the endotracheal tube in the second case, requiring repositioning. Surgical visibility was considered satisfactory when the left lung lobes were collapsed but not optimal when the right lung lobes had to be collapsed because the right cranial lung lobe could not be isolated for anatomical reasons. Both dogs recovered from anaesthesia uneventfully. Anaesthetic management with particular emphasis on the practical use of the EZ‐blocker is reported. Placement of the EZ‐blocker and challenges associated with right lung isolation are described.